CHARACTERISTICS OF CATFISH STOMACH OIL (Clarias gariepinus) REFINED WITH BENTONITE AND ACTIVE CHARCOAL - Dinda Litani Purity; Edison Edison; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTWaste or by-product of catfish (Clarias gariepinus) which is rarely used is stomach.The contents of catfish stomatch is extracted with dry rendering method will produce crudefish oil. Fish oil obtained as a by-product of smoked fish processing often contains a lot ofimpurities, so a purification process is needed using bentonite adsorbents and activatedcharcoal. This study aims to determine the effect of using bentonite adsorbents andactivated charcoal with different concentrations on the characteristics of catfish entrails oil.The method used in this study was an experimental method using a completely randomizeddesign with 3 treatment levels namely bentonite 3%, activated charcoal 7%, and bentonite:activated charcoal (3%:7%). It was repeated 3 times, so that the number of experimentalunits was 9 units. The parameters analyzed were color, odor, and peroxide value. Theresults showed that bentonite and activated charcoal adsorbents had a very significanteffect on the characteristics of catfish entrails oil. The addition of 3% bentonite : 7%activated charcoal produced a better color and smell of fish oil compared to othertreatments. The peroxide value of crude fish oil is 5,18 meq/kg, the peroxide value can bereduced by adding different adsorbents, namely A1(3% bentonite), A2(7% activatedcharcoal), and A3(3% bentonite: 7% activated charcoal). obtained successive results of1.693 meq/kg, 1,62 meq/kg, and 0,776 meq/kg.Keywords:Clarias gariepinus, purification, bentonite, activated charcoal, fish oil1)Student at Faculty of Fisheries and Marine Science, Universitas Riau2)Lecturer atFaculty of Fisheries and Marine Science,UniversitasRiau